2016
DOI: 10.1371/journal.pone.0154784
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Satisfaction, Eating Attitudes and Perceptions of Female Body Silhouettes in Rural South African Adolescents

Abstract: This study aims to examine the associations between BMI, disordered eating attitude, body dissatisfaction in female adolescents, and descriptive attributes assigned to silhouettes of varying sizes in male and female adolescents, aged 11 to 15, in rural South Africa. Height and weight were measured to determine BMI. Age and sex-specific cut-offs for underweight and overweight/obesity were determined using the International Obesity Task Force cut-offs. Body image satisfaction using Feel-Ideal Discrepancy (FID) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 38 publications
3
42
1
5
Order By: Relevance
“…In the present study the young adults were included as participants thinking that they are more concerned about their body image. In a study by Titilola et al, the study participants were adolescents and in the age range of 11-15 years [20]. The M:F in the present study was 1:1.3.…”
Section: Discussionsupporting
confidence: 42%
“…In the present study the young adults were included as participants thinking that they are more concerned about their body image. In a study by Titilola et al, the study participants were adolescents and in the age range of 11-15 years [20]. The M:F in the present study was 1:1.3.…”
Section: Discussionsupporting
confidence: 42%
“…Algunos estudios han encontrado relaciones entre obesidad y percepción de la imagen corporal (Magallares, Carbonero-Carreño, Ruiz-Prieto y Jauregui-Lobera, 2016; Serpa dos Santos, Castillo, Gama de Araujo, & Giménez, 2017). Además, autores como Pedro et al (2016) han relacionado la imagen corporal con el índice de masa corporal (IMC), por lo que las siluetas de imagen corporal podrían ser una forma válida de medir la obesidad en niños, tal y como indicaron Coelho, Padez, Moreira, Rosado y Mourão-Carvalhal (2013) en un estudio en el Cuadernos de Psicología del Deporte, 19, 1 (enero) Sánchez-Castillo, López-Sánchez, Ahmed, Díaz-Suárez.…”
Section: Introductionunclassified
“…Moreover, Pedro et al (2016) reported the connection between body image and the body mass index (BMI). In the same vein, Trejo Ortiz, Castro Veloz, Facio Solís, Mollinedo Montano, & Valdez Esparza (2010) determined that higher values of BMI, especially in women, were connected to a higher bodily dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%